THE INFLUENCE OF VIRTUAL TRY ON, PRODUCT QUALITY, AND COUNTRY OF ORIGIN ON CONSUMER PURCHASING DECISIONS ON MAYBELLINE PRODUCTS - Erneisha Adiesti Septanaya; Alshaf Pebrianggara; Lilik Indayani; Satrio Sudarso (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to examine how consumers' decisions to buy Maybelline goods are influenced by Virtual Try On (VTO), product quality, and location of origin. With the advancement of digital technology, Virtual Try On has emerged as an innovation that facilitates customers' ability to virtually test things before making a purchase. Furthermore, the place of origin and product quality are regarded as significant variables that impact consumer choices. Method: The research method used is quantitative by distributing questionnaires to 100 respondents who have purchased Maybelline products with SPSS version 26 data processing media. This study utilizes non-probability sampling through a purposive sampling approach. Results: The results show that Virtual Try On has a positive and significant effect on purchasing decisions with a T-value of 5.323 and a significance value of 0.001, while product quality does not show a significant effect with a T-value of 1.577 and a significance value of 0.118, and the Country of Origin variable has a positive and significant effect with a T-value of 10.879 and a significance value of 0.001. Novelty: With the advancement of digital technology, Virtual Try On has emerged as an innovation that facilitates customers' ability to virtually test things before making a purchase.